INNOVATIVE ASPECT OF THE TRAINING TECHNOLOGY OF SPORTS AND GAME ACTIVITY - Vera Vasilyevna Vucheva; Olga Nikolaevna Mescheryakova (Вестник Северо-Кавказского федерального университета)
The article considers the problem of improvement of the quality of the education in sphere of «Sports», by application of an innovative technologies of training sports and games activity.